"A Crash Course in Herstory": Remembering the Women's Movement in MAKERS: Women Who Make America. Issue 4 (8th August 2017) - Pruchniewska, Urszula Maria
ABSTRACT: This article explores how the documentary MAKERS: Women Who Make America constructs a collective memory of the women's movement. MAKERS deploys three strategies to present a particular version of the feminist past: the use of individual women as witnesses to the second wave, the use of archival journalism as an "authentic" guide to the past, and the use of narrative to personalize the political. These strategies create an authoritative memory of the women's movement as a narrative of progress that highlights individualism and ends in women's freedom to choose. This collective memory of "feminism as choice" serves as a corrective to negative stereotypes of second-wave feminism; however, it does not effectively mobilize collective feminist action in the present.